2022
DOI: 10.2340/actadv.v102.2401
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Conceptual Framework for a Patient-Reported Impact of Dermatological Diseases (PRIDD) Measure: A Qualitative Concept Elicitation Study

Abstract: Existing patient-reported outcome measures cannot comprehensively capture the full impact of living with a dermatological condition. The aim of this study was to develop a conceptual framework on which to build a new Patient-Reported Impact of Dermatological Diseases (PRIDD) measure. Adults (≥ 18 years of age) living with a dermatological condition, worldwide and/or representatives from a patient organization [AQ2] via a global patient organization network, were invited to an individual or group interview. Dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(28 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…We have shown that existing research largely focuses on specific dermatological conditions, mainly psoriasis followed by eczema. Researchers should aim to develop digital interventions targeting other dermatological conditions, such as hidradenitis suppurativa and acne, which carry a substantial psychological burden ( 8 ), as well as digital interventions that tackle psychological impacts that are common across dermatological conditions. The TIDieR checklist and guide ( 32 ) is likely to be a useful tool for intervention developers to consider when planning, developing, and particularly when reporting, complex digital interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that existing research largely focuses on specific dermatological conditions, mainly psoriasis followed by eczema. Researchers should aim to develop digital interventions targeting other dermatological conditions, such as hidradenitis suppurativa and acne, which carry a substantial psychological burden ( 8 ), as well as digital interventions that tackle psychological impacts that are common across dermatological conditions. The TIDieR checklist and guide ( 32 ) is likely to be a useful tool for intervention developers to consider when planning, developing, and particularly when reporting, complex digital interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatological conditions can impact all aspects of life with people commonly reporting psychological, social, financial, occupational, and educational consequences, plus challenges to daily activities, in addition to their physical manifestations (1)(2)(3)(4)(5)(6)(7)8). Many individuals living with dermatological conditions consider the psychological impact to be most profound (2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This high prevalence carries significant impact on quality of life: There is robust and growing literature on the substantial physical, psychological and social burden for patients and their families. [2][3][4][5][6][7][8][9] Despite this, dermatological diseases are often treated superficially, referred to as 'just a rash', and consequently are overlooked in the global health debate. Open Access funding enabled and organized by Projekt DEAL.…”
Section: Introductionmentioning
confidence: 99%
“…As the first step in new measure development, we collected data via a global qualitative interview study to develop a conceptual framework of impact. 2 We identified 263 areas of impact that cut across diseases and global regions. This work formed, to our knowledge, the basis for the first conceptual framework of the impact of dermatological diseases on patients' lives.…”
Section: Introductionmentioning
confidence: 99%